Effects of oxidative stress, exercise training, and aging in an animal model of autism spectrum disorder - Rogers, Liza (Kansas State University, 2024)
Background: Autism spectrum disorder (ASD) prevalence has increased 175% since 2000 with 1% of the world’s population identified with ASD. Today, ASD affects 1 in 36 children and is characterized by delayed language, motor, and cognitive skills. ASD is characterized by two pillars of pathology: oxidative stress and inflammation. These have been identified as closely related to ASD and many intervention strategies in the literature target these parameters. Purpose: this project will evaluate brain and skeletal muscle oxidative stress via antioxidant expression in a rat model of ASD and the impact of exercise and aging. Methods: Sixteen Long-Evans pregnant rat dams were injected with a single dose of either saline (n=5) or VPA (Sodium Valproate (sigma), 250mg/ml, mixed in saline, 600 mg/kg, n=11). This prenatal exposure to VPA is known to increase the risk of ASD development in offspring. Rats were provided with free access to food and pair-housed with a light cycle of 7 am-7 pm. Rats were enrolled in experiment 1 (exercise study) or experiment 2 (aged ASD study). Experiment 1 animals began a 4-week exercise protocol on the treadmill (Harvard Apparatus, Holliston, MA) on post-natal day 40. Rats ran 5 days a week for 10 minutes at 4.98 m/min, 10 minutes at 7.98 m/min, and 10 minutes at 15.96 m/min for a total of 30 minutes at 0° inclination. Motor coordination was measured with a rotarod both pre and post-intervention. The rod maintained a constant 5rpm speed and the trial ended after 180 seconds. Latency time was recorded for each trial. The littermates of the animals enrolled in the exercise protocol were placed in experiment 2, and aged between 6-18 months to understand the effect of aging on autism. Before the end of life, aged animals performed the Novel Object Recognition task (NOR). Following behavioral testing for both experimental groups, brain and skeletal muscle tissues were collected. Skeletal muscle (soleus, red gastrocnemius) and brain tissue (hippocampi) were homogenized, and western blots were conducted to quantify antioxidant expression. Results: Reduced motor coordination was identified in the experiment 1 VPA groups which was improved with exercise. To confirm an exercise effect, citrate synthase expression was quantified in the soleus muscles. Treadmill-trained animals resulted in higher citrate synthase (CS) activity compared to sedentary animals (p=0.04). Antioxidants superoxide dismutase 1 (SOD1) and catalase were measured in skeletal muscles (experiments 1 & 2), and hippocampi (experiment 2), resulting in declines to antioxidant expression in experiment 1 animals (p<0.05), and declines in aged male antioxidant expression (p<0.05). Conclusion: The protective effect of exercise against ASD pathology is important to understand both in its use as a therapy but also as a tool to highlight the protective pathways.
Keywords: Autism; Exercise; Muscle; Aging